(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
“Nono” is an indigenous fermented milk product. Handlers’ poor sanitary cultures and non-scientific practices harm food safety and public health. This study evaluated the microbiological, physicochemical, and sensory properties of "Nono," collected from the marketplaces of Enugu North Senatorial District of Nigeria. The total aerobic bacterial and total coliform counts were higher than Nigeria’s standard value whereas, 50% of the overall fungal count was within permissible limits regardless of market samples. The bacteria identified were Staphylococcus aureus (17.65%), Salmonella enterica (17.65%), Bacillus subtilis (11.76%), Klebsiella aerogenes (11.76%), whereas fungal were Aspergillus niger (57.14%) and Torulopsis dottila (42.86%). Although significant changes (P < 0.05) in proximate and physicochemical parameters were observed, no significant differences in sensory attributes (P > 0.05) across these samples were recorded. The means (±SD) for pH (4.47±0.18), protein (8.74±0.44%) etc. were recorded. The presence of pathogenic bacteria in the nono samples could be hazardous to public health. Bangladesh J. Sci. Ind. Res. 60(2), 93-106, 2024